Endometriosis: Correlation of Severity of Pain with Stages of Disease - Chowdhury, Tanzeem S; Mahmud, Nusrat; Chowdhury, TA (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Objective: To assess the prevalence and severity of pain in patients with endometriosis and to evaluate the relationship between the severity of pelvic pain with different stages of endometriosis. Methods: A prospective observational study conducted among 65 patients diagnosed with endometriosis during surgery in Infertility Management Center Dhaka, a specialized center for treatment of infertility and assisted reproductive technologies from January 2008 to January 2009. Result: Majority of the patients were between 26-30 years. Pelvic pain was the predominant symptom in 78.5% patients and the rest were asymptomatic. Among the symptomatic patients, most common symptom was dysmenorrhoea (n=47, 92.1%).When severity of pain was graded; it was observed that most (37%) presented with moderate pain. Infertility was present in 85% patients, mostly (n- 47 =74%) in primary sub fertility group. The commonest site of endometriosis was uterosacral ligament (n-58=89%) and ovarian endometriosis is noted in (63%) cases. Most of the lesions (35%) were black, haemosiderin deposits. When r-ASRM staging system was applied, majority (58.4%) of the patients was in stage IV disease and most of the patients (31%) with endometrioma were in stage IV disease. The study revealed a strong positive correlation between severe pain and stage IV disease (Correlation co efficient 0.711). Moderate forms of pain and severity of disease did not show any positive correlation in this study (Correlation co efficient 0.390). There was negative correlation between milder forms of pain with severity of disease. Conclusion: There was no relationship between frequency and severity of pain symptoms and disease stage of endometriosis. J Bangladesh Coll Phys Surg 2016; 34(3): 135-139